Semaphorin-4D signaling in recruiting dental stem cells for vascular stabilization - Lili Zhang; Dineshi Sewvandi Thalakiriyawa; Jiawei Liu; Shengyan Yang; Yan Wang; Waruna Lakmal Dissanayaka (Stem Cell Research & Therapy)
Abstract Background Achieving a stable vasculature is crucial for tissue regeneration. Endothelial cells initiate vascular morphogenesis, followed by mural cells that stabilize new vessels. This study investigated the in vivo effects of Sema4D-Plexin-B1 signaling on stem cells from human exfoliated deciduous teeth (SHED)-supported angiogenesis, focusing on its mechanism in PDGF-BB secretion. We also explored macrophages as an endogenous source of Sema4D for vascular stabilization. Methods The in vivo Matrigel plug angiogenesis assay was conducted to examine the impact of Sema4D on vessel formation and stabilization supported by SHED. Knockdown of Plexin-B1 in human umbilical vein endothelial cells (HUVECs) and PDGFR-β inhibitors were utilized to explore the fundamental regulatory mechanisms. Furthermore, the m6A methylation levels of total RNA and the expression of Methyltransferase-like 3 (METTL3) were assessed under conditions of Sema4D treatment in vitro. An ELISA was employed to measure the levels of Sema4D in the supernatants derived from THP-1 cell-mediated macrophages. Additionally, a three-dimensional vasculature-on-a-chip microfluidic device was used to investigate the role of M2c macrophage-derived Sema4D in the stabilization of vascular structures. Results Sema4D induced the formation of a greater number of perfused vessels by HUVECs and enhanced the coverage of these vessels by SM22α-positive SHED (SM22α+SHED). Conversely, the knockdown of the Plexin-B1 receptor in HUVECs or inhibition of PDGFR-β reversed the Sema4D-induced vascular stabilization, thereby confirming the regulatory role of the Plexin-B1/PDGF-BB axis in the recruitment of mural cells mediated by Sema4D. Mechanistically, Sema4D was found to upregulate the expression of methyltransferases, specifically METTL3, and to elevate the level of m6A modification in HUVECs. This modification was determined to be critical for enhancing PDGF-BB secretion, suggesting that Sema4D activates an epigenetic regulatory mechanism. Additionally, we investigated the secretion of Sema4D by various macrophage phenotypes, identifying that M2c macrophages secrete significant levels of Sema4D. This secretion recruited SM22α+SHED as mural cells by inducing endothelial PDGF production on a vasculature-on-a-chip platform, indicating a potential role for macrophages in facilitating vascular stabilization. Conclusions Sema4D acts on Plexin-B1, inducing METTL3-mediated PDGF-BB secretion to recruit SHED to stabilize vessels. Macrophages could be a key source of Sema4D for vascular stabilization.